Structural Enhancement in Shallow Gas Cloud Region Structural Enhancement in Shallow Gas Cloud Region - A H Abdul Latiff, D P Ghosh, S N F Jamaludin, . (2015)
This research will address the issue of poor structural interpretation below complex overburden and shallow anomaly that cause wave field distortion. The main objective of this research paper is to present the result of seismic interpretation over a seismic line extracted from a shallow gas filed located in Malay Basin.